Genetic characterization of the human relapsing fever spirochete Borrelia miyamotoi in vectors and animal reservoirs of Lyme disease spirochetes in France - Jean-François Cosson; Lorraine Michelet; Julien Chotte; Evelyne Le Naour; Martine Cote; Elodie Devillers; Marie-Lazarine Poulle; Dominique Huet; Maxime Galan; Julia Geller; Sara Moutailler; Muriel Vayssier-Taussat (Parasites & Vectors, 2014)
Abstract Background In France as elsewhere in Europe the most prevalent TBD in humans is Lyme borreliosis, caused by different bacterial species belonging to Borrelia burgdorferi sensu lato complex and transmitted by the most important tick species in France, Ixodes ricinus. However, the diagnosis of Lyme disease is not always confirmed and unexplained syndromes occurring after tick bites have become an important issue. Recently, B. miyamotoi belonging to the relapsing fever group and transmitted by the same Ixodes species has been involved in human disease in Russia, the USA and the Netherlands. In the present study, we investigate the presence of B. miyamotoi along with other Lyme Borreliosis spirochetes, in ticks and possible animal reservoirs collected in France. Methods We analyzed 268 ticks (Ixodes ricinus) and 72 bank voles (Myodes glareolus) collected and trapped in France for the presence of DNA from B. miyamotoi as well as from Lyme spirochetes using q-PCR and specific primers and probes. We then compared the French genotypes with those found in other European countries. Results We found that 3% of ticks and 5.55% of bank voles were found infected by the same B. miyamotoi genotype, while co-infection with other Lyme spirochetes (B. garinii) was identified in 12% of B. miyamotoi infected ticks. Sequencing showed that ticks and rodents carried the same genotype as those recently characterized in a sick person in the Netherlands. Conclusions The genotype of B. miyamotoi circulating in ticks and bank voles in France is identical to those already described in ticks from Western Europe and to the genotype isolated from a sick person in The Netherlands. This results suggests that even though no human cases have been reported in France, surveillance has to be improved. Moreover, we showed that ticks could simultaneously carry B. miyamotoi and Lyme disease spirochetes, increasing the problem of co-infection in humans.